2015
DOI: 10.1371/journal.pcbi.1004054
|View full text |Cite
|
Sign up to set email alerts
|

Membrane-Mediated Interaction between Strongly Anisotropic Protein Scaffolds

Abstract: Specialized proteins serve as scaffolds sculpting strongly curved membranes of intracellular organelles. Effective membrane shaping requires segregation of these proteins into domains and is, therefore, critically dependent on the protein-protein interaction. Interactions mediated by membrane elastic deformations have been extensively analyzed within approximations of large inter-protein distances, small extents of the protein-mediated membrane bending and small deviations of the protein shapes from isotropic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
85
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(86 citation statements)
references
References 59 publications
(111 reference statements)
1
85
0
Order By: Relevance
“…Previous analysis of the membrane-mediated interaction of two strongly elongated scaffolds, r a [ r b , has shown that for relevant values of the transverse curvature, c b , the scaffolds mutually orient such that their long axes tend to be parallel to each other and perpendicular to the line connecting their centers (26). In addition, the scaffolds exhibit a long-range attraction and short-range repulsion resulting in an equilibrium distance between them, which is comparable to the scaffold dimension (26). While the membrane-mediated forces between multiple scaffolds are not pairwise (28), their qualitative features should be similar to those of the two-scaffold interactions.…”
Section: Scaffold Shapementioning
confidence: 99%
See 2 more Smart Citations
“…Previous analysis of the membrane-mediated interaction of two strongly elongated scaffolds, r a [ r b , has shown that for relevant values of the transverse curvature, c b , the scaffolds mutually orient such that their long axes tend to be parallel to each other and perpendicular to the line connecting their centers (26). In addition, the scaffolds exhibit a long-range attraction and short-range repulsion resulting in an equilibrium distance between them, which is comparable to the scaffold dimension (26). While the membrane-mediated forces between multiple scaffolds are not pairwise (28), their qualitative features should be similar to those of the two-scaffold interactions.…”
Section: Scaffold Shapementioning
confidence: 99%
“…The convergence of the optimization conditions, the error estimations, and the accuracy criteria of the calculations have been described in our previous study of a two-scaffold system (26).…”
Section: Energy Landscapementioning
confidence: 99%
See 1 more Smart Citation
“…It was also shown that anisotropic inclusions experience interactions of longer range than isotropic ones and are able to produce complex aggregates [29,30]. To simplify the theoretical calculations, membrane inclusions are usually modelled as non-deformable objects with a fixed curved shape [30][31][32][33]. Owing to their small sizes it is often convenient to treat them as point-like objects [30,31,34].…”
Section: Introductionmentioning
confidence: 99%
“…The classical Canham-Helfrich curvature free energy [32,33] has been extended to anisotropic curvatures [34][35][36]. To simplify the interactions, the protein and membrane underneath it have been often modeled together as an undeformable object with a fixed curved shape such as a point-like object with an anisotropic curvature [37,38] and a bent elliptical surface [39]. Furthermore, it has also been clarified that two undeformable parallel rods have an attractive interaction but the interaction is repulsive for a perpendicular orientation.…”
Section: Introductionmentioning
confidence: 99%